Statistical Modeling for the Anticipation of Tension In-Hospital Emergencies - Nouha MHIMDI; Wahiba BEN ABDESSALEM KARAA; Henda BEN GHEZALA (Communications of International Proceedings, 2021)
Following unexpected exceptional events (corona virus, natural disaster, heat wave) that have appeared in recent decades, the emergency services are experiencing poor management of immediate patient care, especially in stress cases. The number of victims in hospitals has increased from time to time because of the significant insufficiency of human and material resources, the medical staff is very frequently confronted with situations of peak activity each period. Often, traditional health resources are overwhelmed, ineffective and unable to manage the situation of tension. Thus, in this paper, we use a mathematical model in order to predict the stress level in the emergency services. Real was gathered near these establishments.
Keywords: Tension; Anticipation; Data processing; Statistical model.